REMEMBERING NATHAN H. AZRIN - LATTAL, KENNON A. (Mexican Journal of Behavior Analysis, 2013)
Short of his mentor and the discipline´s founder, B.F. Skinner, it is difficult to think of anyone who has a broader impact on both the science and application of behavior analysis than Nathan H. Azrin, whose long career spanning seven decades ended with his death on MAy 18, 2013. Nate´s contributions to both experimental and applied behavior analysis, and the discipline´s acknowledgements of these accomplishiments, are a matter of record.